Exploring preferences for variable delays over fixed delays to high-value food rewards as a model of food-seeking behaviours in humans. (18th February 2019) - Stokes, Laura-Jean G.; Davies, Anna; Lattimore, Paul; Winstanley, Catharine; Rogers, Robert D.
Abstract : Foraging and operant models suggest that animals will tolerate uncertainty or risk to obtain food quickly. In modern food environments, sustained access to quick energy-dense foods can promote weight gain. Here, we used a discrete-choice procedure to examine peoples' decisions about when next to eat high-value, palatable food rewards, probabilistically delivered immediately or following longer delays. In Experiment 1, moderately hungry young females showed consistent preferences for a variable delay option that delivered food rewards immediately or following long delays over a fixed delay option that delivered the same rewards following intermediate delays. These preferences were stronger in females with higher BMIs compared with lower BMIs, suggesting that quick food can enhance the value of uncertain or 'risky' food-seeking strategies in individuals vulnerable to future weight gain. In Experiment 2, prior exposure to a subtle and not easily identifiable food aroma increased selections of the variable delay option following delayed food rewards in a mixed sample of male and female adults, providing preliminary evidence that food cues can sustain uncertain food-seeking strategies. These data highlight a working hypothesis that the rapid delivery and consumption of food rewards, and food cues, can increase risk-tolerance in the food-seeking behaviours of individuals who are vulnerable to weight gain. This article is part of the theme issue 'Risk taking and impulsive behaviour: fundamental discoveries, theoretical perspectives and clinical implications'.